Manajemen Hakim (Studi Perbandingan Indonesia dengan Turki) - Azhar, Ikhsan (Faculty of Law, Mulawarman University, 2018)
In the past three years, the profession as a judge has been in the spotlight. The reason is because this profession can be referred to as